EFFECT OF CASING MATERIAL MANAGEMENT ON YIELD AND YIELD ATTRIBUTES OF MILKY WHITE MUSHROOM (CALOCYBE INDICA) - Ahmed, Ferdaus; Rahman, Jahedur; Islam, Nazrul; Ullah, Jafar; Sarker, Nirod Chandra (International Journal of Research -GRANTHAALAYAH, 2020)
General practice in Bangladesh is, after harvest producers leave the non-effective fruiting body of milky white mushroom in the spawn packet as it is. But every fruiting body primordia take some nutrient from the substrate, and the dried & rotten primordia may encourage other competitive fungi or harmful microorganism to grow on the upper surface of the substrate which may affect the fruiting body formation and yield in the subsequent flushes. Therefore, the present study was under taken to know the effect of casing material management technique on yield and yield attributes of milky white mushroom. Five different casing material management technique were practiced in this experiment, such as T1= removal of dried non effective fruiting bodies after each harvest; T2= removal of dried non effective fruiting bodies and filling the casing hole with fresh casing material after each harvest; T3= scraping the upper surface of the substrate after each harvest; T4= scraping the upper surface of the substrate and adding 10% fresh casing material after each harvest; and T5= no disturbance of the casing material (control). Number of effective fruiting body (NEFB), number of flushes, days to total harvest and size of fruiting body were significantly affected by casing material management technique but economic yield and biological efficiency among the treatments were insignificant. Considering all the parameters removal of dried non effective fruiting bodies and filling the casing hole with fresh casing material after each harvest (T2) was the best technique for casing material management.